Pertumbuhan dan Hasil Kailan (Brassica oleraceae Var Alboglabra L. H. Bailey) Pada Pemberian Pupuk Organik Cair Limbah Kulit Buah di Tanah Gambut - M.D. Wahyuningtyas; Siti Zubaidah; Ici Pieter Kulu (Jurnal Kaharati, 2022)
This study aims to: 1). to determine the effect of organic fertilizer application of fruit peel waste on the growth and yield of kailan plants on peat soil; 2). to know the organic fertilizer that gives the best growth and yield of kailan plants on peat soil; 3). to determine the best dose of organic fertilizer for fruit peel waste on the growth and yield of kailan plants on peat soil.The study was conducted using a Non-factorial Completely Randomized Design (CRD), with 10 levels of treatment, each treatment being repeated 3 times so that 30 experimental units were obtained. This research was conducted in a green house with a plastic roof on Langkai Village, Pahandut District, Palangka Raya City, Central Kalimantan, from May to July 2021. The results showed that the application of liquid organic fertilizer from fruit peel waste had no significant effect on all observation parameters but liquid organic fertilizer of pineapple peel waste 20 ml plant-1 gave the best results at plant fresh weight of 90.44 g and total chlorophyll content of 0.38 mg g-1. Liquid organic fertilizer from banana peel waste at a dose of 20 ml plant-1 gave the best growth with 8.53 leaves, 11.16 g root weight and 897.87 cm2 leaf area.